Uptake of acid black 210 dye by organo-montmorillonite clay minerals - Volzone, Cristina (2013)
Two clays rich in montmorillonite were modified and used as adsorbents. The clay minerals were modified with hexadecylpyridinium cation (HDP⁺) in order to obtain organo-montmorillonites, which were used for retaining acid black 210 dye from water solution. This dye is frequently used in tanning industry. The retentions of the anionic dye by organo-montmorillonites were evaluated by using complete UV-visible spectrum, analyzing the concentrations of dye solutions before (50 mg/L) and after the contact with the adsorbent. The solids were characterized by X-ray diffraction (XRD) and infrared analyses (FT-IR). The interlayer spacing of the montmorillonites increased, after organic cation exchange, from 13.0-14.9 Å to 19.0-22.0 Å and allowed the uptake of acid black 210 dye. The most disordered arrangement of HDP in montmorillonite, deduced by XRD and FT-IR analyses, was better for higher retentions of acid black dye.